Penerapan Unsur Tindak Pidana Pasal 379a KUHP “Penipuan sebagai Mata Pencaharian” - David Bani Adam; Safar Dwi Kurniawan; Arif Rakhman (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the implementation and proof of elements of criminal acts as required by Article 379a of the Criminal Code, specifically in cases where fraud is used as a livelihood. A normative legal approach is used with an analysis of legal documents and court decisions. The two results show the main aspects: (a) objective evidence in the form of transmission of fraud patterns and similar modes of use, and (b) subjective evidence in the form of intensity to make the activity a source of life. The findings show that recognition of habits (elements of habits) and completeness of evidence are key in the application of this article. The novelty of the study is the integration between empirical conclusion data and the need for proof of economic actors' habits, a dimension that has been less explored in previous studies.